The Study Traits of Adolescents in the Literature for Adolescents on “Pho Maha, Mae Hang Khrueang, Look Sao Nak Rong” of Chot Srisuwan-Author - Kunlabutdee, Chamaiphorn; Untaya, Sopee (Ratchaphruek Journal, 2021)
This research aimed to study traits of adolescence from the literature foradolescentson Pho Maha, Mae Hang Khrueang, Look Sao Nak Rong of ChotSrisuwan-author. The method using in this research was the studying from the document literature 12-18 years from the Office of the Basic Education Commission, Ministry of Education. The analysis was based on the concepts of adolescents and linguistic devices. Sample were 12-18 years teenager book category in fiction fromthe Office of the Basic Education Commission, Ministry ofEducation from the year 2004-2020, 57 subjects were selected with one specific study the best book of the year 2019. The results revealed that there were five traits of adolescent in the literature: 1) Need to be superiorthan others; 2) Being aggressive behavior and willfulness; 3) Focus on materialism and transliteration; 4) Lack of responsibility; and 5) Need more freedom. These traits are presented through five linguistic strategies were lexical choices, conditional sentences, rhetorical question, modality and presupposition.